Resultados do transplante alogênico de células tronco hematopoiéticas em síndrome mielodisplásica do Hospital Universitário Walter Cantídio - Cordeiro, Missielle Duarte (2022)
Introduction: Myelodysplastic syndromes (MDS) are a heterogeneous group of clonal hematopoietic disorders that are more likely to progress to acute myeloid leukemia (AML). Alogenic Haematopoietic Stem Cell Transplantation (HSCT) represents the most effective curative treatment for MDS to date. Objectives: To describe the profile of patients with MDS, who performed HSCT at the Walter Cantídio Universitary Hospital (HUWC) in Fortaleza, Ceará. Methodology: Retrospective observational and descriptive study with eleven patients with newly diagnosed MDS who performed HSCT in the period of February, 2015 to June, 2018. Results: Total of eleven patients, age at diagnosis from nineteen to sixty-six years (mean age 46 years). Three deletion patients of the 5q (two with additional alterations), four hypocellular, one with multiple lineage dysplasia (p53 positive in immunohistochemistry), two with excess type 2 blasts, one with ring sideroblasts (low risk). Ten related donors with peripheral blood cell source and one non-related source of bone marrow. Deaths: a patient with excess blasts and a patient with multilinear dysplasia. Conclusion: It is possible to identify patients with low-risk MDS who have an indication for Alogenic Hematopoietic Stem Cell Transplantation. Additional cytogenetic abnormalities at the 5q deletion had no negative impact. We also reinforced the prognostic significance of p53.